Automatic molecular collection and detection by using fuel-powered microengines. Issue 17 (19th April 2016) - Han, Di; Fang, Yangfu; Du, Deyang; Huang, Gaoshan; Qiu, Teng; Mei, Yongfeng
Abstract : Self-propelled catalytically-powered microengines rolled-up from nanomembranes work as collecting and transporting molecules in fluids for surface-enhanced Raman scattering detection. Abstract : We design and fabricate a simple self-powered system to collect analyte molecules in fluids for surface-enhanced Raman scattering (SERS) detection. The system is based on catalytic Au/SiO/Ti/Ag-layered microengines by employing rolled-up nanotechnology. Pronounced SERS signals are observed on microengines with more carrier molecules compared with the same structure without automatic motions.